EFEKTIFITAS PENERAPAN SEGMENTATION, TARGETING DAN POSITIONING TERHADAP PENJUALAN PRODUK INDIHOME PT. TELKOM INDONESIA - Sri Mulyani; Misharni; Syofria Meidona (Universitas Sumatera Barat, 2021)
This research aims to determine the Segmentation, Targeting, Positioningstrategies at PT.Telkom Indonesia,Tbk Witel west Sumatra. This type of research used in thisresearch is descriptive qualitative research. The research was conducted ad PT. TelkomIndonesia, Tbk Witel Sumatra by selecting 3 informants who were consideredrepresentatives of the group consisting of 1 key informant. Namely the CC employees and 2non-key informants, the data collection techniques used in this study were in-depthinterviews and observation. The results showed that a targeted marketing strategy woild beable to assist companies in delivering products to consumers according to their wants andneeds. One of which is by implementing a segmentation strategy, targeting, and positioning.